Analysis of Educational Benefits Children Girls Suku Laut in Panglima Raja Village of Concong District Indragiri Hilir Regency - Haryono, Haryono; Separen, Separen; Rahim, Habibi (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This study entitled Analysis of Benefits of Education for Orang Laut Children Girls in the Panglima RajaVillage District of Concong, Indragiri Hilir Regency. The author is interested to examine the problem because of the low number of Orang Laut Children girls who enter the world of education. This study was conducted with the aim to find out whether for Orang Laut education girls it has benefits. This research uses Descriptive Quantitative research method, by using the formula: P = f / n x 100%. Population in this research is all Parent and daughter of Orang Laut which amount to 30 people, because this research is research population so entire population become sample in this research. While the data were collected using questionnaires, interviews and observations and research results indicated that the hypotheses in this study were accepted or proven, because 50% of girls thought education was less useful and this was reinforced by the preparation of Sutrisno Hadis opinion that the role was less if ranged from 0% -33.33%, While the magnitude of educational benefits for marine tribal girls based on research results Only 28.57%.